2019
DOI: 10.1182/blood.2018893750
|View full text |Cite
|
Sign up to set email alerts
|

Hydroa vacciniforme–like lymphoproliferative disorder: an EBV disease with a low risk of systemic illness in whites

Abstract: Patients with classic hydroa vacciniforme–like lymphoproliferative disorder (HVLPD) typically have high levels of Epstein-Barr virus (EBV) DNA in T cells and/or natural killer (NK) cells in blood and skin lesions induced by sun exposure that are infiltrated with EBV-infected lymphocytes. HVLPD is very rare in the United States and Europe but more common in Asia and South America. The disease can progress to a systemic form that may result in fatal lymphoma. We report our 11-year experience with 16 HVLPD patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 28 publications
5
70
1
2
Order By: Relevance
“…We found that race and the age at onset were correlated with the prognosis of patients with HVLPD, which is consistent with the results reported by Cohen [11]. Compared with the patients in Cohen's study, our patients had a higher tendency to progress to systemic diseases, and their main manifestations were persistent fever and involvement of the lymph nodes, lungs, liver and spleen.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that race and the age at onset were correlated with the prognosis of patients with HVLPD, which is consistent with the results reported by Cohen [11]. Compared with the patients in Cohen's study, our patients had a higher tendency to progress to systemic diseases, and their main manifestations were persistent fever and involvement of the lymph nodes, lungs, liver and spleen.…”
Section: Discussionsupporting
confidence: 91%
“…HVLPD shares many common features with EBV T/NK cell lymphoproliferative diseases or CAEBV without HVLPD, including high levels of EBV DNA in the blood (primarily inTor NK cells) and a high frequency of clonal T cells. However, EBV T/NK cell lymphoproliferative diseases and CAEBV without HVLPD are more fatal [11]. Thus, distinguishing HVLPD from EBV T/NK cell lymphoproliferative diseases or CAEBV without HVLPD is very important.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, over 90% of patients with classic HV or atypical/severe HV have elevated γδ T-cell percentages > 5%, and all HV patients have a high EBV DNA load, although there were no statistically significant differences between classic versus atypical/severe HV [35]. By realtime quantitative reverse transcription polymerase chain reaction (qRT-PCR) and flow cytometry immunophenotypic analysis, Cohen et al described elevated levels of EBV DNA in the blood and high levels of EBV DNA in T or NK cells in all HVLPD patients, without any significant differences between patients with classic versus atypical/severe HV [17]. Compared to classic HV patients, atypical/severe HV patients more frequently had abnormal antibody profiles to EBV antigens, such as elevated antiviral capsid antigen (VCA),elevated anti-early antigen (EA) and low EBV nuclear antigen (EBNA), and the serologic patterns were consistent with chronic active EBV infection [9].…”
Section: Clinical Manifestations and Laboratory Characteristicsmentioning
confidence: 99%
“…Classic HV-LPD was originally described in the Caucasian population and is characterized by a photodermatosis originating as vesicles, evolving to crusts and leaving varicelliform scars after healing [1][2][3][4]. Systemic symptoms are usually not observed and this benign condition normally improves with sun avoidance and resolves spontaneously in adolescence [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Systemic hydroa vacciniforme (HV) typically affects children and adolescents from Asia and Latin America [1][2][3][4]. This generally presents as a more severe cutaneous condition; however, systemic features including constitutional symptoms, hepatosplenomegaly and lymphadenopathy are also present.…”
Section: Introductionmentioning
confidence: 99%